Targeting Histone Deacetylase 11 with a Highly Selective Inhibitor for the Treatment of MASLD - Feng Zhang; Kairui Yue; Simin Sun; Shengyuan Lu; Geng Jia; Yang Zha; Shuang Zhang; C. James Chou; Chenzhong Liao; Xiaoyang Li; Yajun Duan (Advanced Science)
Abstract Metabolic dysfunction‐associated steatotic liver disease (MASLD) represents the most prevalent chronic liver disorder globally. Due to its intricate pathogenesis and the current lack of efficacious pharmacological interventions, there is a pressing need to discover novel therapeutic targets and agents for MASLD treatment. Herein, it is found that histone deacetylase 11 (HDAC11), a subtype of HDAC family, is markedly overexpressed in both in vitro and in vivo models of MASLD. Furthermore, the knockdown of HDAC11 is observed to mitigate lipid accumulation in hepatic cells. A highly selective HDAC11 inhibitor, B6, which exhibits favorable pharmacokinetic property and liver distribution, is further designed and synthesized. Integrating RNA‐seq data with in vivo and in vitro experiments, B6 is found to inhibit de novo lipogenesis (DNL) and promote fatty acid oxidation, thus mitigating hepatic lipid accumulation and pathological symptoms in MASLD mice. Further omics analysis and experiments reveal that B6 enhances the phosphorylation of AMPKα1 at Thr172 through the inhibition of HDAC11, consequently modulating DNL and fatty acid oxidation in the liver. In summary, this study identifies HDAC11 as a potential therapeutic target in MASLD and reports the discovery of a highly selective HDAC11 inhibitor with favorable drug‐like properties for the treatment of MASLD.